Formation of the sea passenger transportation market and cruise tourism industry - Kolomiyets, K.; Nefedova, N.; Molodetskiy, A.; Prykhodko, Z.; Shashero, A. (Journal of Education, Health and Sport, 2023)
The article is devoted to the emergence, development and current state of sea passenger transportation. The main stages of development of sea passenger transportation, characteristics of vehicles, difficulties that arose during the operation of passenger vessels are presented. The factors that contributed to the development and industry of sea cruises are analyzed. The issues of gradual transformation of sea cruises into tourist entertainment of mass tourism are considered.